Thrombin-Independent Activation of Platelet Factor XIII by Endogenous Platelet Acid Protease - Lynch, Garry W; Pfueller, Sharron L (Thrombosis and Haemostasis, 1988)
Platelets contain factor XIII, an A subunit zymogen form of transglutaminase (TGase), that is activated by thrombin. In addition a thrombin-independent TGase (A#) was observed. A# was formed in platelet preparations lysed at acid pH, and its generation inhibited by protease inhibitors and alkaline pH. When maximal A# activity was generated in acidified lysates no further TGase activity could be induced by subsequent treatment with thrombin. Both FXIII zymogen and A# copurified as for F XIII, from either alkaline or from acidified platelet lysates respectively, by the conventional procedure. The pH optima, Km’s for NN dimethyl casein, molecular weights, heat lability of active forms, requirements for calcium and reducing agents, and immunological characteristics of both TGases were the same. Studies with inhibitor substrates suggested that a thrombin-like cathepsin C or carboxypeptidase was responsible for A# formation. Purified F XIII zymogen could be activated directly by cathepsin C. Thus, the predominant, and probably only, TGase of platelets is factor XIII, which may be activated either by thrombin or by endogenous platelet acid protease(s).
Keywords: Platelet factor XIII; Transglutaminase; Acid protease; Cathepsin